1992
DOI: 10.1002/neu.480230308
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol pulses induce progestin receptors selectively in substance P‐immunoreactive neurons in the ventrolateral hypothalamus of female guinea pigs

Abstract: Low doses of estradiol, administered as pulses, are as effective as higher doses for priming ovariectomized (OVX) guinea pigs to display progesterone-facilitated lordosis. High doses of estradiol, administered by constant-release implants, induce progestin receptors in many substance P-immunoreactive (SP-IR) neurons in the ventrolateral hypothalamus (VLH), a site at which estradiol primes OVX guinea pigs to respond behaviorally to progesterone. To test the hypothesis that behaviorally effective estradiol pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The proportion of PR-IR neurons that also had SP-IR (39%) observed in this study is within the range of those previously reported (2,6). By adding together the mean percentages of PR & SP-IR neurons retrogradely labeled by each of the four injections, we can account for the projections of about 58% of this group of VLH neurons.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The proportion of PR-IR neurons that also had SP-IR (39%) observed in this study is within the range of those previously reported (2,6). By adding together the mean percentages of PR & SP-IR neurons retrogradely labeled by each of the four injections, we can account for the projections of about 58% of this group of VLH neurons.…”
Section: Discussionsupporting
confidence: 88%
“…The pattern of immunostaining for both progestin receptors and substance P matched previous reports (2,6). VLH sections (Figure 1 ) were analyzed from three guinea pigs for each type of injection site (Table 1 ).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, FluoroGold injections into the dorsal midbrain labeled a large proportion (approximately 30%) of the vl VMN neurons immunoreactive for SP in the guinea pig (Ricciardi & Blaustein 1994). Furthermore, pulsatile administration of estradiol selectively induces the expression of progesterone receptors in SP neurons located in this area (Olster & Blaustein 1992), and this process is necessary for the induction of lordosis (Rubin & Barfield 1983). Collectively, these results suggest that SP originating in the vl VMN may participate in the onset of lordosis behavior (Dornan et al 1990), however, further detailed components of the anatomy and physiology of this neurocircuitry is missing.…”
Section: Substance Pmentioning
confidence: 99%
“…Because reproductive hormone levels cycle in female rats, however, constant-release pellets cannot be considered physiological. Indeed, daily or continuous peripheral administration of low estradiol doses or even single high doses of long-lasting estrogens such as estradiol valerate can disrupt ovarian cycling, induce pseudopregnancy, elicit progressive, aphysiological changes in several brain neurochemical receptor systems and in behavior, and greatly accelerate the degeneration of the arcuate nucleus (83,179,347,467,468,528,529,647). In contrast, a weekly cyclic estradiol injection regimen in which 10 g estradiol benzoate was injected on Tuesdays and Wednesdays and progesterone priming and sexual-receptivity tests were done on Fridays led to stable, normal levels of progestin and oxytocin receptors and in sexual receptivity (647).…”
Section: Physiological Sex Differences In Disordered Eating)mentioning
confidence: 99%